El Excentrico, 1969-04-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
April 5, 1969 [5 de abril de 1969]. No volume or issue number. Cover has picture of John De Heras, who was running fir City Coucilman. The headline reads, "Vote for John De Heras, D.C., San Jose City Councilman Seat 5, Thursday, April 8."